(untitled) (Microbiologia Medica, 2025)
Medically relevant Corynebacterium species include Corynebacterium diphtheriae, and non-diphtherial Corynebacteria. A part of the normal flora of the skin and mucous membranes, non-diphtherial Corynebacteria, which is frequently dismissed as a contaminant, has an important role in clinical disease. In the last decades, the pathogenicity among other Corynebacterium spp. has been increasingly reported. This case report presents a rare occurrence of faucial diphtheria caused by Corynebacterium striatum in a 13-year-old female patient. Molecular analysis confirmed C. striatum, which was non-toxigenic by Elek’s gel precipitation test. This case underscores the need for heightened awareness of non-diphtherial Corynebacteria as emerging pathogens, their diagnosis and accurate treatment.